Pengaruh Penggunaan E-Commerce, Financial Technology dan Media Sosial Terhadap Peningkatan Pendapatan UMKM di Jawa Tengah - Widodo Wibisono; Sri Heneng Prasastono; Mohammad Hidayatul Holili (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research aims to study and analyze the factors of e-commerce, financial technology and social media on increasing the income of MSMEs in Central Java with the help of the SPSS computer application in conducting testing.This research uses a type of research, namely descriptive quantitative. The quantitative descriptive research method is an approach that aims to explain phenomena or events as they really are through the collection and analysis of numerical data. This method is used to objectively identify the characteristics, frequencies and relationships between variables in a population or sample.The results obtained in this research have 3 hypotheses in the form of H1, H2 and H3, namely H1 and H2 are declared rejected where the e-commerce and Financial Technology variables have no influence on increasing MSME income in Central Java while H3 is accepted where the social media variable has an influence towards increasing income.